Preprints are good for science and good for the public - Sarabipour, Sarvenaz; Wissink, Erin M.; Burgess, Steven J.; Hensel, Zach; Debat, Humberto Julio; Emmott, Edward; Akay, Alper; Akdemir, Kadir C.; Schwessinger, Benjamin (Nature Research, 2020)
We disagree with Tom Sheldon’s contention that the preprint ecosystem can present a challenge to accurate and timely journalism (Nature 559, 445; 2018). Restricting when or how preprints are released risks suppressing science communication without any clear advantage to the public. When scientists and journalists follow fundamental principles for reporting.